Reverse Total Shoulder Arthroplasty without Bone-Grafting for Severe Glenoid Bone Loss in Patients with Osteoarthritis and Intact Rotator Cuff: A Concise 5-Year Follow-up of a Previous Report*. (7th April 2021) - McFarland, Edward G.; Meshram, Prashant; Rojas, Jorge; Joseph, Jacob; Srikumaran, Uma
Abstract : Abstract: We previously reported on 40 patients (42 shoulders) with glenoid bone loss who underwent reverse total shoulder arthroplasty with glenoid reaming and without bone-grafting. The purpose of this study was to report the updated results in 29 patients (31 shoulders) from the original cohort who were available after a minimum 5-year follow-up. Since the last report, 1 additional patient had a baseplate failure. The cumulative incidence of baseplate failure requiring revision, accounting for the competing risk of death, was 2.4% (95% confidence interval [CI], 0.2% to 12%) at 2 years and 5.2% (95% CI, 0.9% to 16%) at 5 and 10 years. Patients who did not have an implant failure had a statistically significant and clinically relevant improvement compared with their preoperative scores on a visual analog scale (VAS) for pain, American Shoulder and Elbow Surgeons (ASES) score, Simple Shoulder Test, and Short Form-36 (SF-36). Scapular notching occurred in 6 shoulders (19%). For the studied indication, reaming the glenoid flat produced excellent prosthetic survival with clinical results maintained at a minimum 5-year follow-up. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.